(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study was conducted to analyze some factors related to anemia and iron deficiency anemia among pregnant women in Kien Duc commune, Lam Dong province. Methods: A cross-sectional descriptive study was conducted on 208 pregnant women attending antenatal care at the Dak R’Lap regional Medical Center from April 2025 to May 2025. Data were collected through interviews and hematological tests (hemoglobin, ferritin). Multivariate regression analysis was used to identify associated factors. Results: The overall prevalence of anemia was 17.3%; the prevalence of iron deficiency anemia was 9.6%. Regression analysis showed that the method of taking iron tablets was significantly associated with anemia (p < 0.001); specifically, the group taking iron with milk/calcium had a lower risk of anemia than the group taking it with plain water (PR = 0.51). For iron deficiency anemia, a history of miscarriage was a significant risk factor (p < 0.001). Conclusions: A history of miscarriage is a strong predictor of iron deficiency anemia, while habits related to iron supplementation are associated with general anemia. These findings highlight the need for prioritized screening and nutritional counseling for pregnant women with a history of miscarriage.